A historical perspective on informal institutional and international entrepreneurship - Jiawen Chen; Linlin Liu (Humanities & Social Sciences Communications, 2023)
Abstract In this paper, a historical perspective is taken to investigate the variations in institutional and international entrepreneurship that occur throughout Africa. Drawing on the institutional theory of international entrepreneurship, we introduce ethnic fractionalization as an informal institution that influences new venture internationalization in African countries. Further, we identify the historical traumatic shock exerted by the epidemic disease spread by tsetse flies as the driver of the relationship between ethnic fractionalization and new venture internationalization. Based on a sample of 33,621 firm-year observations covering 40 African countries, Our empirical findings provide important insights into international entrepreneurship in Africa and offers a theoretical extension into the historical origins of informal institutions.